Differences between successful and unsuccessful basketball teams on the final olympic tournament - Pojskic, H.; Separovic, V.; Uzicanin, E. (Acta Kinesiologica, 2009)
The aim of the study was to find out global quantitative differences between successful and unsuccessful teams, which had played on the Olympic basketball tournament, in twenty two standard and derived statistical indicators of situational efficiency. The research was performed on the sample of 37 matches, so that 74 different statistical samples have been included in analysis. Data were collected by means of statistics patterns provided by official FIBA web site www.fiba.com. A discriminative analysis has been conducted in order to track down possible differences between two groups of the teams. One statistically significant discriminative function has been obtained. The values of canonical correlation are pretty high, which is to say that the 22 statistical parameters make very good difference between successful and unsuccessful teams, but also that there were big differences between the groups. The obtained results show that assists, parameters of shooters` field goal efficiency, defensive rebound and number of points made by bench players are variables that make the most significant difference between victorious and defeated teams. The reason for big differences between the victorious and defeated national teams that participated on the final Olympic basketball tournament in Beijing is probably because they highly differentiated in technical, tactical and physical conditioning, what is conditioned by participation of various quality national teams that come from different continents and countries, where basketball leagues are not so good.